A USER LOYALTY ANALYSIS OF MOBILE INSTANT MESSAGING (MIM) APPLICATIONS IN MANADO - Soselisa, Rico Maurits Corneles; Mekel, Peggy Adeline; Pandowo, Merinda (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
The growth of Mobile Instant Messaging (MIM) applications in Indonesia has become a prevalent phenomenon as it gradually has replaced the existence of traditional messaging tools such as SMS. With the emergence of these mobile instant messaging applications, consumers are inundated with choices as to which application should they install on their phones. Therefore, User loyalty is crucial to the survival of MIM application providers. Population of this research is users of MIM applications and/or people who are aware of the development of MIM applications in Manado, under the age of 30. This research employs exploratory method on qualitative research and interview as the tool to collect all data and information with informant as many as 6 informants. The internal factors i.e.: speed of loading, public image, loyalty program, intriguing features, user-friendly, price-friendly, post-installation care, and qualified product. The external factors i.e.: existence of a community, mobile internet network quality, ubiquitous connectedness, age group, and peer influence. This research suggests MIM providers to improve user loyalty by putting the same amount of effort into the advancement of both internal and external factors, as the MIM industry is highly dependent on the external factors as the findings suggested. Â  Keywords: user loyalty, MIM application